Circumventing Novice Teacher Imbroglio in Kenya: A Proposed Mentorship Program - Kailiti, Hellen B. K (IJRDO- Journal of Educational Research, 2017)
Novice teachers, in primary and secondary schools, in Kenya face a myriad of problemsand challenges in the early stages of their teaching career. As much as they have gone through thecolleges, when they embark on teaching, they realize that they have inadequate knowledge, skillsand attributes to handle learners. In most cases, there is little support from other teachers and withtime, negative experiences erode the confidence of beginning teachers over time, leading to highattrition rate. Sometimes, beginning teachers a face reality shock as the theories learned duringtheir training do not fit neatly into the real-world teaching practice even for though they haveundertaken teaching practice. In the first year of training, many beginning teachers are givenresponsibilities out of the classroom which they have to undertake, even when they did not learnabout the tasks involved. Sometimes, the veteran teachers have less responsibilities and they havetime to informally supervise the beginning teachers. Most beginning teachers are enthusiasticabout the work but after experiencing frustration and alienation from the veteran teachers, theygradually lack morale and end up having very little achievement as far as learning outcomes areconcerned. When teachers are thrust into the profession without proper guidance in place, theystruggle on their own to make learners to perform well in exams and other activities. A welldesignedmentorship program can enable teachers to adapt well to the profession and be motivatedenough to motivate the learners. This paper conceptualizes a plan for teacher mentoring in Kenya. If adopted, the model can be used to improve the performance of beginning teachers or teacherson new assignments